Validation of GWAS-Identified Variants for Anti-TNF Drug Response in Rheumatoid Arthritis - Sánchez-Maldonado, Jose Manuel (2021)
Funding Information: We thank all participants who have agreed to participate in this study. Authors also thank Mar?a Dolores Casares, ?ngeles Molina, Carmen Oloriz for the collection of Spanish samples and Hans Jurgen Hoffmann, Marianne Thomsen, Vibeke ?stergaard Thomsen, Malene Rohr Andersen, Lise Lotte B. Laursen, Helle J?rgensen, Ram Benny Christian Dessau, Niels Steen Krogh, Ulla Vogel, Paal Skytt Andersen, Ivan Brandslund, Steffen Bank, Frederik Trier M?ller, Nikolai Toft and Niels M?ller Andersen for the participation in collection and purification of Danish samples. We also thank the Danish Departments of Rheumatology for their implication in the collection of clinical data from RA patients included in the DANBIO cohort and the Danish Rheumatologic Biobank. Likewise, we would like to thank Teun van Herwaarden for steroid hormone measurements in serum samples from subjects ascertained through the HFGP initiative. Publisher Copyright: Copyright © 2021 Sánchez-Maldonado, Cáliz, López-Nevot, Cabrera-Serrano, Moñiz-Díez, Canhão, Ter Horst, Quartuccio, Sorensen, Glintborg, Hetland, Filipescu, Pérez-Pampin, Conesa-Zamora, Swierkot, den Broeder, De Vita, Petersen, Li, Ferrer, Escudero, Netea, Coenen, Andersen, Fonseca, Jurado, Bogunia-Kubik, Collantes and Sainz.